Task Force Consensus on Nosology and Cut‐Off Values for Axial Postural Abnormalities in Parkinsonism. Issue 5 (9th May 2022) - Tinazzi, Michele; Geroin, Christian; Bhidayasiri, Roongroj; Bloem, Bastiaan R.; Capato, Tamine; Djaldetti, Ruth; Doherty, Karen; Fasano, Alfonso; Tibar, Houyam; Lopiano, Leonardo; Margraf, Nils G.; Merello, Marcelo; et al.
ABSTRACT: Background: There is no consensus with regard to the nosology and cut‐off values for postural abnormalities in parkinsonism. Objective: To reach a consensus regarding the nosology and cut‐off values. Methods: Using a modified Delphi panel method, multiple rounds of questionnaires were conducted by movement disorder experts to define nosology and cut‐offs of postural abnormalities. Results: After separating axial from appendicular postural deformities, a full agreement was found for the following terms and cut‐offs: camptocormia, with thoracic fulcrum (>45°) or lumbar fulcrum (>30°), Pisa syndrome (>10°), and antecollis (>45°). "Anterior trunk flexion, " with thoracic (≥25° to ≤45°) or lumbar fulcrum (>15° to ≤30°), "lateral trunk flexion" (≥5° to ≤10°), and "anterior neck flexion" (>35° to ≤45°) were chosen for milder postural abnormalities. Conclusions: For axial postural abnormalities, we recommend the use of proposed cut‐offs and six unique terms, namely camptocormia, Pisa syndrome, antecollis, anterior trunk flexion, lateral trunk flexion, anterior neck flexion, to harmonize clinical practice and future research.